Impact of screen time on early childhood’s eating behavior: A review - Lumban Gaol, Riama Claudia Christine; Rahmiwati, Anita; Hasyim, Hamzah (Riset Informasi Kesehatan, 2025)
Background: The excessive of screen time use among early childhood has become a phenomenon. In Indonesia, early childhood that has used screen time is around 68.01% for watching television, 33.44% using cellphones, and 24.96% have accessed the internet. The use of screen time among early childhood should be reduced because it can affect children to have lower nutrition that can lead to malnutrition and other metabolic disease. Method: This research method uses literature review with a narrative approach. The reference article was conducted on databases in Google Schoolar and PubMed. Results: The impact of excessive screen time use on early childhood’s eating behavior can cause the unhealthy food consumption and picky eating. This behavior will affect children to have lower nutrition that can lead to malnutrition and other metabolic disease. Conclusion: The use of excessive screen time on early childhood can impact the child’s eating behavior.